Associations between neuropsychiatric symptoms and cognition in Chinese patients with amyotrophic lateral sclerosis. Issue 5 (17th August 2016) - Wei, Qianqian; Chen, Xueping; Cao, Bei; Ou, Ruwei; Zhao, Bi; Wu, Ying; Shang, Huifang
Abstract: Our objective was to explore features of the neuropsychiatric symptoms in Chinese patients with amyotrophic lateral sclerosis (ALS) and the associations between these neuropsychiatric symptoms and cognition. A total of 91 ALS patients were evaluated using three recommended scales including the Neuropsychiatric Inventory (NPI), Addenbrooke's Cognitive Examination Revised (ACE-R), and Frontal Assessment Battery (FAB) tests. The mean age of onset was 52.5 ± 10.8 years. The median NPI score of all patients was 2.0. The most common neuropsychiatric symptom was dysphoria/depression (59.3%), followed by anxiety (41.8%) and irritability/lability (26.4%). There were no significant differences in the frequency of neuropsychiatric symptoms in terms of gender, age of onset, onset form and disease duration. There were no significant differences in NPI total score, ACE-R total score and FAB total score in terms of gender, age of onset, onset form and disease duration, except for a higher ACE-R score observed in patients with a shorter disease duration. The NPI score had a strong correlation with the ACE-R score but not with the FAB score. In conclusion, neuropsychiatric symptoms appear to be quite common in Chinese ALS patients, who were likely to present with the emotional states of depression or anxiety. The neuropsychiatric symptoms in ALS are closely related to global cognition dysfunction.